Wave-packet continuum-discretization approach to single ionization of helium by antiprotons and energetic protons - Abdurakhmanov, Ilkhom; Kadyrov, Alisher; Bray, Igor; Bartschat, K. (American Physical Society, 2017)
© 2017 American Physical Society. The recently developed wave-packet continuum-discretization approach [I. B. Abdurakhmanov, A. S. Kadyrov, and I. Bray, Phys. Rev. A 94, 022703 (2016)2469-992610.1103/PhysRevA.94.022703] is extended to antiproton-helium collisions. The helium target is treated as a three-body Coulomb system using a frozen-core approximation, in which the electron-electron correlation within the target is accounted for through the static interaction. The Schrödinger equation for the helium target is solved numerically to yield bound and continuum states of the active electron. The resulting continuum state is used to construct wave-packet pseudostates with arbitrary energies. The energies of the pseudostates are chosen in a way that is ideal for detailed differential ionization studies. Two-electron target wave functions, formed from the bound and continuum wave-packet states of the active electron and the 1s orbital of He+, are then utilized in the single-center semiclassical impact-parameter close-coupling scheme. A comprehensive set of benchmark results, from angle-integrated to fully differential cross sections for antiproton impact single ionization of helium in the energy range from 1 keV to 1 MeV, is provided. Furthermore, we use our single-center convergent close-coupling approach to study fully differential single ionization of helium by 1-MeV proton impact. The calculated results are in good agreement with recent experimental measurements [H. Gassert, O. Chuluunbaatar, M. Waitz, F. Trinter, H.-K. Kim, T. Bauer, A. Laucke, C. Müller, J. Voigtsberger, M. Weller, Phys. Rev. Lett. 116, 073201 (2016)PRLTAO0031-900710.1103/PhysRevLett.116.073201] for all considered geometries.